The The Impact of Super Golden Ratio Implementation on User Satisfaction: A Study of Horizontal Scrolling in Bacana User Interface (UI) Design - Farizah Farha Mahdi; Andi Jamiati Paramita; Furqan Zakiyabarsi; Hany Alexandra Philemon; Rena Nainggolan; Fenina Adline Twince Tobing (IJNMT (International Journal of New Media Technology), 2025)
Abstract— Low reading interest in Indonesia (0.001%) demands innovation in digital literacy applications like Bacana. However, Bacana's current interface remains conventional, potentially limiting user satisfaction. This study aims to evaluate the implementation of the Super Golden Ratio (ψ≈1.4656) and horizontal scrolling navigation to enhance aesthetics and user experience. The research method involved instrument testing with high reliability (Cronbach’s α>0.94) and linear regression analysis. The results indicate that all regression assumptions were met, showing no heteroscedasticity or autocorrelation, with a significant linear relationship (p<0.001). Empirical findings prove that the combination of the Super Golden Ratio and horizontal scrolling effectively improves readability, interaction smoothness, and user satisfaction. This study provides a strategic contribution to UI/UX development for literacy applications by utilizing mathematical ratios to achieve better visual harmony and navigational efficiency.